Analisis Kepuasan Pengguna Aplikasi Dramabox Pada Kalangan Generasi Z Kota Jambi Menggunakan Metode End User Computing Satisfaction (EUCS) - Elisa, Vioren; Assegaff, Setiawan; Aryani, Lies (Prosiding Seminar Nasional Ilmu Teknik, 2025)
The development of video streaming services has made DramaBox widely used by Generation Z, who prioritize fast entertainment access through mobile devices. However, complaints such as long ad duration, unstable video quality, and inaccurate subtitles remain obstacles that can reduce user satisfaction. This study analyzes the factors that influence DramaBox user satisfaction in Jambi City using the End User Computing Satisfaction (EUCS) method with five main dimensions: content, accuracy, format, ease of use, and timeliness. Data were obtained through questionnaires completed by 385 respondents and processed using SEM-PLS with the help of SmartPLS 4. The results showed that accuracy and timeliness significantly influence user satisfaction, while content, format, and ease of use did not have a significant impact. This finding indicates that information reliability and system speed are the most determining aspects of user experience. Therefore, improvements in both aspects are important for the future development of the DramaBox application.